4(6x-1)=2(1-3x)

Simple and best practice solution for 4(6x-1)=2(1-3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(6x-1)=2(1-3x) equation:



4(6x-1)=2(1-3x)
We move all terms to the left:
4(6x-1)-(2(1-3x))=0
We add all the numbers together, and all the variables
4(6x-1)-(2(-3x+1))=0
We multiply parentheses
24x-(2(-3x+1))-4=0
We calculate terms in parentheses: -(2(-3x+1)), so:
2(-3x+1)
We multiply parentheses
-6x+2
Back to the equation:
-(-6x+2)
We get rid of parentheses
24x+6x-2-4=0
We add all the numbers together, and all the variables
30x-6=0
We move all terms containing x to the left, all other terms to the right
30x=6
x=6/30
x=1/5

See similar equations:

| (4x+8)°=(6x-6)° | | 7x^2-6x-1680=0 | | 5t2+26t-24=0 | | 6x+3x–x+9=33. | | 20×y=300,y=160 | | 5x–3=x–15 | | 8x+30=5x–6 | | 0=-2x(6-x) | | x3−5x2+3x+10=5 | | -2x(6-x)=0 | | 2x+1/4x-3/5=1/4x | | (x-1)(x+2)=(2x-3)(x+2) | | X+1/x-2/3=1/2 | | 3x+1/2-4x-1/3=1 | | X+2÷5=x-4÷2 | | 10=20-2n | | X-3/2=4x+3/3 | | 144x-81=0 | | -0.4n+3.6=12.8 | | 3x+7x-10=7+10x-17 | | 4x+7=9+5 | | 2,5x=1000 | | 2x–4=7x+10 | | -7,x-2,8=-6,6-9x | | -40x^2+20x+20=0 | | 1/3y−12=38 | | 64/8=n/128 | | 6x-12=5+(2x-9) | | (5,-3)m=4 | | 2x+3=4(x-2)+8 | | -11=5(m-3) | | 3x–4=7x+4 |

Equations solver categories